The importance of hair in the identity of Black people - Lashley, Myrna (Nouvelles pratiques sociales)

(untitled) (Université du Québec à Montréal, 2020)
Hairstyles have always been important to Black Africans and their descendants and are important in expressing identity. The transatlantic slave trade made it difficult to maintain these hairstyles, mostly due to separation from familial and other ties. Since Black phenotypes were viewed as inferior, Black hair and styles were seen as ugly and unacceptable. The American Civil Rights Movement (ACRM) ushered in a resurgence in ‘natural’ hairstyles, supporting a collective identity and a counterhegemonic movement. However, the success of this movement did not propel Black hairstyles on to the same plane as those that maintained the imperial aesthetic of the white ideal. The constant diminution of the Black identity through the disparagement of Black hairstyles has been used as a synonym for racism and can lead to psychological distress and mental instability. Although Black people have resided in Canada and Quebec since the 17th century, there is very little in Canadian academic literature addressing these issues. This theoretical paper presents a discourse on the importance of hair to the identity of Black people and will add to the limited literature by providing Canadian and Québécois institutions with a greater appreciation of the prominence of Black hair and hairstyles to the identity and well-being of Black people.